PENILAIAN KINERJA KEUANGAN BERDASARKAN PERATURAN BANK INDONESIA - Fatmah Watty Pelupessy (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The Assessment of Bank Health on Bank Indonesia Regulation No. 6 / 10 / PBI /2004 (A Study Of Branchs Offices of PT. Bank Maluku). The objective of researchis to analyze the financial performance of all branch offices of PT BankPembangunan Daerah Maluku based on PBI No. 6/10/PBI/2004 in the 2007-2010period. Data analysis tool is CAMELS. The population in this study were allbranches of Bank Maluku, and based on purposive sampling technique thenobtained a sample of eight branch offices. Some results are indicated. First, allbranch offices of PT Bank Pembangunan Daerah Maluku are in good category, butstill having minor weaknesses which are solvable by periodic action, Second, theobservation of the main branch in 2010 shows that the bank is relatively good butwith some weaknesses which are capable to reduce its composite rank unless thebank are taking immediate corrective action..